Physical Linkage of Estrogen Receptor α and Aromatase in Rat: Oligocrine and Endocrine Actions of CNS-Produced Estrogens - Storman, Emiliya M (Endocrinology, 2018)
Rapid-signaling membrane estrogen receptors (mERs) and aromatase (Aro) are present throughout the central nervous system (CNS), enabling acute regulation of CNS estrogenic signaling. We previously reported that spinal membrane Aro (mAro) and mERα oligomerize (1). As their organizational relationship would likely influence functions of locally produced estrogens, we quantified the mAro and mERα that are physically associated and nonassociated in two functionally different regions of rat CNS: the spinal cord, which has predominantly neural functionalities, and the hypothalamus, which has both neural and endocrine capabilities. Quantitative immunoprecipitation (IP), coimmunoprecipitation, and Western blot analysis were used to quantify the associated and nonassociated subpopulations of mAro and mERα. Regardless of estrous-cycle stage, virtually all mAro was oligomerized with mERα in the spinal cord, whereas only ∼15% was oligomerized in the hypothalamus. The predominance of nonassociated mAro in the hypothalamus, in combination with findings that many hypothalamic Aro-immunoreactive neurons could be retrogradely labeled with peripherally injected Fluoro-Gold, suggests that a portion of hypothalamic estrogens is secreted, potentially regulating pituitary function. Moreover, circulating estrogens increased hypothalamic Aro activity (quantified by the tritiated water-release assay) in the absence of increased Aro protein, revealing nongenomic regulation of Aro activity in the mammalian CNS. The demonstrated presence of associated and nonassociated mAro and mERα subpopulations in the CNS suggests that their selective targeting could restore impaired estrogen-dependent CNS functionalities while minimizing unwanted effects. The full physiological ramifications of brain-secreted estrogens remain to be explored.